The Role of Non-Coding RNAs in Uveal Melanoma - Bande, Manuel (Cancers (Basel), 2020)
SIMPLE SUMMARY: The development of uveal melanoma is a multifactorial and multi-step process, in which abnormal gene expression plays a key role. Recently, several studies have highlighted the role of non-coding RNAs in the progression of uveal melanoma by affecting different signaling pathways. As important agents in the regulation of genes, non-coding RNAs have enormous potential to open up therapeutic pathways, predict response to treatment, and anticipate patient outcome for uveal melanoma. This review aims to provide a comprehensive view of what we know about ncRNAs in uveal melanoma currently. ABSTRACT: Uveal melanoma (UM) is the most common primary intraocular tumor in adulthood. Approximately 50% of patients develop metastatic disease, which typically affects the liver and is usually fatal within one year. This type of cancer is heterogeneous in nature and is divided into two broad groups of tumors according to their susceptibility to develop metastasis. In the last decade, chromosomal abnormalities and the aberrant expression of several signaling pathways and oncogenes in uveal melanomas have been described. Recently, importance has been given to the association of the mentioned deregulation with the expression of non-coding RNAs (ncRNAs). Here, we review the different classes of ncRNAs—such as long non-coding RNAs (lncRNAs) and microRNAs (miRNAs)—and their contribution to the development of UM. Special attention is given to miRNAs and their regulatory role in physiopathology and their potential as biomarkers. As important agents in gene regulation, ncRNAs have a huge potential for opening up therapeutic pathways, predicting response to treatment, and anticipating patient outcome for UM.